Effects of Surface-Bound Collagen-Mimetic Peptides on Macrophage Uptake and Immunomodulation - Rowley, Andrew T.; Meli, Vijaykumar S.; Wu-Woods, Natalie J.; Chen, Esther Y.; Liu, Wendy F.; Wang, Szu-Wen (Frontiers in Bioengineering and Biotechnology, 2020)
The interaction between collagen/collagen-like peptides and the commonly-expressed immune cell receptor LAIR-1 (leukocyte-associated immunoglobulin-like receptor-1) regulates and directs immune responses throughout the body. Understanding and designing these interactions within the context of biomaterials could advance the development of materials used in medical applications. In this study, we investigate the immunomodulatory effects of biomaterials engineered to display a human collagen III-derived ligand peptide (LAIR1-LP) that targets LAIR-1. Specifically, we examine the effects of LAIR1-LP functionalized surfaces on uptake of polymeric particles and cell debris by macrophages polarized towards inflammatory or healing phenotypes. We observed that culture of macrophages on LAIR1-LP functionalized surfaces increased their uptake of PLGA micro- and nano-particles, as well as apoptotic fibroblasts, while reducing their secretion of TNFα in response to LPS/IFNγ pro-inflammatory stimulation, when compared to cells seeded on control surfaces. To investigate the role of LAIR-1 in the observed LAIR1-LP-induced effects, we used siRNA to knock down LAIR-1 expression and found that cells lacking LAIR-1 exhibited enhanced particle uptake on LAIR1-LP and control surfaces. Furthermore, analysis of gene expression showed that LAIR-1 knockdown led to increase expression of other receptors involved in cell uptake, including CD-36, SRA-1, and beta-2 integrin. Together, our study suggests that LAIR1-LP enhances macrophage uptake potentially through interactions with collagen-domain binding surface receptors, and inhibits inflammation through interaction with LAIR-1.